Parenteral Treatment of Multiple Sclerosis: The Advent of Monoclonal Antibodies - Singer, Barry A. (Seminars in Neurology, 2016)
Improved disease control is critical for enhancing the lives of those living with multiple sclerosis. With specific immunologic targets, monoclonal antibody (mAb) treatments are highly effective options for relapsing forms of multiple sclerosis. The mechanism, efficacy, and current safety profiles are detailed for the two mAb therapies, natalizumab and alemtuzumab, with regulatory approval in multiple countries. Daclizumab, which targets the interleukin-2 receptor, and ocrelizumab, which depletes B cells, have convincing phase 3 clinical trial data and may very well provide new options in the near future. Trial results of other B-cell-directed therapies, ofatumumab and rituximab, are reviewed. Less-frequent dosing of glatiramer acetate and interferon β-1a highlight developments in the first generation of parenteral immunomodulatory therapy. Remyelination using mAbs has moved into clinical trials with the first agents, anti-LINGO-1, rHIgM22, and anti-SEMA 4D.
Keywords: monoclonal antibody; multiple sclerosis; alemtuzumab; daclizumab; ocrelizumab